Can individual investors identify economic links? Evidence from initial quarterly earnings announcements within industries. Issue 1 (2nd January 2020) - Luo, Yilin; Hong, Jianqiao; Ni, Chenkai; Wang, Guochen
ABSTRACT: We examine whether individual investors in China have the ability to acquire and process the information of industry peers. We exploit the initial earnings announcement within each industry-quarter during 2015-2017 and use the frequency of investors' daily discussions on the Xue Qiu platform to capture their information acquisition activities. We find that non-announcing firms' investors exhibit a significant increase in their discussion frequency around the initial earnings announcement within an industry. These increased discussions facilitate the information transfer from the announcing firm to its non-announcing peers, manifested by the latter's reactions in share prices and trading volume to the former's unexpected earnings. In the cross-section, investors' acquisition and processing of peer information are more pronounced when non-announcing firms exhibit a worse information environment or a stronger economic link with the announcing firm. Collectively, individual investors in China exhibit some rationality in acquiring and utilizing information of economically linked firms.